2016
DOI: 10.1111/bcpt.12566
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Partial α2‐Adrenoceptor Agonist and Pure α2‐Adrenoceptor Antagonist on the Behavioural Symptoms of Withdrawal after Chronic Alcohol Administration in Mice

Abstract: As an addictive drug, alcohol produces withdrawal symptoms if discontinued abruptly after chronic use. Clonidine (CLN), a partial a 2 -adrenergic agonist, and mirtazapine (MRT), an antagonist of a 2 -adrenoceptor, both clinically aid alcohol withdrawal. Considering different mechanisms of action of the two drugs, this study was designed to see how far these two mechanistically different drugs differ in their ability to decrease the severity of ethanol withdrawal syndrome. The effect of CLN and MRT on ethanol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(61 reference statements)
0
4
0
1
Order By: Relevance
“…In an early rat study in which alcohol dependence was induced by repeated intragastric alcohol administration, clonidine suppressed withdrawal signs, whereas yohimbine, which increases norepinephrine levels, exacerbated withdrawal (Trzaskowska and Kostowski, 1983). Subsequent studies have shown that a 2 -adrenergic agonists decrease somatic signs of alcohol withdrawal in animal models (Parale and Kulkarni, 1986;Riihioja et al, 1997), including responses that are associated with hyperkatifeia, such as the clonidine-induced blockade of anxiogenic-like effects of alcohol withdrawal in mice (Arora and Vohora, 2016). The a 2 -adrenergic agonists decreased alcohol intake in Finnish Alko alcohol rats that had free-choice access to 10% alcohol and drinking water (Opitz, 1990).…”
Section: B Between-system Neuroadaptations: Norepinephrinementioning
confidence: 99%
“…In an early rat study in which alcohol dependence was induced by repeated intragastric alcohol administration, clonidine suppressed withdrawal signs, whereas yohimbine, which increases norepinephrine levels, exacerbated withdrawal (Trzaskowska and Kostowski, 1983). Subsequent studies have shown that a 2 -adrenergic agonists decrease somatic signs of alcohol withdrawal in animal models (Parale and Kulkarni, 1986;Riihioja et al, 1997), including responses that are associated with hyperkatifeia, such as the clonidine-induced blockade of anxiogenic-like effects of alcohol withdrawal in mice (Arora and Vohora, 2016). The a 2 -adrenergic agonists decreased alcohol intake in Finnish Alko alcohol rats that had free-choice access to 10% alcohol and drinking water (Opitz, 1990).…”
Section: B Between-system Neuroadaptations: Norepinephrinementioning
confidence: 99%
“…Unlike with studies of anxiety‐like behavior, inconsistent findings regarding depressive‐like behavior during acute withdrawal have been reported, and results appear to be significantly dependent on the method of EtOH administration and to some extent, the behavioral assay utilized. In mice, forced methods of EtOH administration (Arora and Vohora, 2016; Karadayian et al, 2013; Metten et al, 2018), as opposed to long‐term voluntary consumption paradigms (Holleran et al, 2016; Lee et al, 2015; Lee et al, 2016; Lee et al, 2017; Stevenson et al, 2009), seem to more reliably produce depressive‐like behavior during acute withdrawal. Nonetheless, there is abundant evidence for the presentation of depressive‐like behavior in mice during early abstinence, across various methods of EtOH administration and behavioral assays (Gong et al, 2017; Holleran et al, 2016; Kim et al, 2017; Pang et al, 2013; Roni and Rahman, 2017; Stevenson et al, 2009).…”
mentioning
confidence: 99%
“…Clonidine is a non-opioid drug, that is a partial agonist of alpha 2 -adrenergic receptors ( Giovannitti et al, 2015 ; Arora and Vohora, 2016 ). It was used in opioid substitution treatment over the years ( Jamadarkhana and Gopal, 2010 ).…”
Section: Discussionmentioning
confidence: 99%